New Ways of Materials Engineering Implementation in the Selection Processes of Biomaterials Intended for the Production of Dental Implants – Narrative Literature Review - Jan DUPLAK; Darina DUPLAKOVA; Dusan MITAL; Zuzana MITALOVA (Medžiagotyra, 2023)
The usage of knowledge obtained by connecting various scientific areas provides new opportunities for developing multidisciplinary branches to improve processes, procedures, technologies, and products. The present paper is devoted to the description of new approaches to material engineering and its possibilities in the process of the selection of materials intended for the production of dental implants. To ensure the conciseness of the article, a selection of state-of-the-art of scientific contributions is created in the introductory part in the form of a summary table, based on which the following parts of the article are elaborated. The first view of new ways of materials engineering is provided through the elaboration of the categorization of the setting of biological materials used in the production of dental implants, while taking into account current trends, technologies and findings. The second view of new ways of materials engineering is an extended complex process of selection and implementation of biomaterials intended for the production of dental implants originally created and adopted by the American Dental Association. Future studies should investigate the comprehensive analysis of technologies for the production of dental implant materials and also analysis of ways of digitization in the production of dental implants.